Analysis of the Instruction Question Language in the Arabic Textbook for Class X Islamic Senior High School Published by the Ministry of Religion of Indonesia/ Analisis Bahasa Intruksi Soal pada Buku Ajar Bahasa Arab kelas X Madrasah Aliyah Terbitan Kemenag Indonesia - Ahmad Yasir Amrulloh; Ana Nurjannah; Muhammad Alfan (Journal of Arabic Language Studies and Teaching, 2021)
Abstract This study aims to determine the quality of language instruction in the class X Madrasah Aliyah Arabic textbook published by the ministry of religion in 2020 by referring to the language instruction criteria for question practice according to Rusydi Ahmad Thuaimah and the Directorate of Islamic Education. The research method is descriptive qualitative with the Miles and Huberman model. Data found 53 kinds of exercise instructions in four maharah with data results: 1) using Arabic fusha, there are 53 items, 2) the point instruction language used easily to understand there are 53 points, 3) unambiguous there are 51 points, 4) giving examples of how to do it, there are 8 points, 5) using correct and standard language rules, there are 49 points, 6) using communicative language there are 53 points. Thus, the instructions for practising questions in the book are very suitable to be used as a reference in making exercise instructions.